(DIS)KONTINUITA ČEŠTINY 16.-18. STOLETÍ NA PŘÍKLADU HLÁSKOSLOVÍ - ŠIMEČKOVÁ, MARTA (Slavia Occidentalis, 2020)
A majority of the earlier scholarly publications (literary and linguistic) contain negative assessments of the Czech language from the 17th and 18th centuries. This valuation is in accordance with the political, social, religious and cultural developments in Bohemia after the battle of White Mountain (Bílá hora) on 8 November 1620. Following the battle, the Habsburg Monarchy was established and Bohemia was yet again subjected to the Catholic Church. The function of the Czech language was limited with German becoming the main language spoken by the Bohemian aristocracy and city dwellers. German was the official language and, along with Latin, the language of science. As a result of the functional restrictions, Czech books were printed in limited literary fields, especially religious, historical and practically-oriented texts. The language in which they were written was described as degraded, unstable and incorrect. It was connected with the decline of the standard language, deformed by dialectisms, neologisms and an enormous number of loan words from German. However, is this interpretation of the Czech language from the 17th and 18th centuries correct? I have analysed over 100 prints from the 16th to the 18th centuries, focusing on four phonological phenomena: prothetic v-, dipthongisation ú- > ou- and ý (í) > ej and the change é > í. These changes occurred in texts from the 16th century (or even earlier), then some of them were repressed (ej, í in word ending, prothetic v-) or fixed as a part of Czech print (initial ou-, v- by words stabilized with this nonetymological consonant). It is evident that 1) there was continuous development instead of discontinuity, 2) the earlier negative estimation of the Czech language after 1620 was inaccurate. It is imperative to investigate the Czech language from a historical perspective in detail, without prejudice or ideology.